Implikatur Percakapan dalam Film Mangkujiwo Karya Azhar Kinoi Lubis Serta Implementasinya Terhadap Pembelajaran Bahasa Indonesia Di SMA - Hidayat, Rohmat; Farid, Edi Kurniawan; Hamdiah, Magfirotul (Universitas Negeri Padang, 2024)
This research aims to describe the conversational implicatures in the film Mangkujiwo by Azhar Kinoi Lubis. This study was motivated by the large number of fans and viewers of this film. In this film, there are many conversations that contain implicatures, either in the form of sarcasm or criticism. In this research, researchers used a pragmatic approach. This type of research is descriptive qualitative. The data used in this research is the conversation in the film Mangkujiwo by Azhar Kinoi Lubis. The results of this research on the data obtained, found 10 data containing implicatures, 9 data containing implicatures which are satirical sentences, and 1 data which is a critical sentence.Keywords: Conversational implicature, Mangkujiwo film by Azhar Kinoi Lubis.